'Money Spinners': R. Seifert & Partners, Sir Frank Price and Public-Sector Speculative Development in the 1970s. (21st September 2018) - Harrison, Ewan
Abstract: This article examines an unexecuted example of the work of the prolific architectural practice R. Seifert & Partners designed for a site in central Birmingham in the 1970s. R. Seifert & Partners worked largely for developer clients, and this type of speculative architecture has been little studied by historians of the period. The particular example of the practice's work examined here reveals a complex network of architects, planning facilitators and client organisations that, crucially, spanned the public and private sectors.